Intelligent System for Student Performance Prediction Using Machine Learning - S. Ibrahim Alsumaidaie, Mustafa; Adil Nafea, Ahmed; Abbas Mukhlif, Abdulrahman; D. Jalal, Ruqaiya; M AL-Ani, Mohammed (Majallat Baghdād lil-ʻulūm, 2024)
يعتمد الذكاء الاصطناعي (AI) على الخوارزميات التي تمكن الآلات من اتخاذ قرارات بدلاً من البشر، مما يؤدي إلى تحسين تجارب المستخدم عبر مجالات متنوعة. تناقش هذه الدراسة حلاً ذكيًا للتنبؤ بأداء الطلاب وتحديد الطلاب الذين قد يحتاجون إلى دعم إضافي. يستخدم النظام المقترح خوارزميات التعلم الآلي الخاضع للإشراف: مصنف الغابة العشوائية، ومصنف الأشجار الإضافية، ومصنف. تتضمن منهجية البحث جمع البيانات والمعالجة المسبقة وتحديد الميزات وبناء النموذج والتقييم. يتم استخدام مجموعة بيانات مكونة من 24000 مثيل للتدريب و6000 مثيل للاختبار. يتم تطبيق تقنيات المعالجة المسبقة على مجموعة البيانات، ويتم استخدام خوارزميات تعلم الآلة للكشف عن أداء الطلاب. تقوم النماذج المدربة بتقييم نتائج الطلاب بناءً على استفسارات المستخدم. ويتم تقييم دقة وكفاءة النظام المقترح باستخدام المقاييس المناسبة. تحقق خوارزمية ET أعلى دقة تبلغ 98.15%، تليها خوارزمية RF بنسبة 94.03% وKNN بنسبة 91.65%. تُظهر مقاييس الدقة والاستدعاء قيمًا عالية عبر الخوارزميات الثلاثة. تعرض KNN وقت تدريب أقل بكثير يبلغ 0.00 ثانية، مما يوضح كفاءتها الحسابية. بشكل عام، توفر هذه الورقة رؤى فعالة حول تطبيق تعلم الآلة في التنبؤ بأداء الطلاب. يُظهر النموذج المقترح نتائج واعدة في تحديد الطلاب الذين يحتاجون إلى دعم إضافي، مما يتيح التدخلات المناسبة لتعزيز نتائجهم الأكاديمية. تساهم النتائج في التنقيب عن البيانات التعليمية في العراق ولها آثار على تحسين معدلات نجاح الطلاب في المؤسسات التعليمية. Accurately predicting student performance remains a significant challenge in the educational sector. Identifying students who need additional support early can significantly impact their academic outcomes. This study aims to develop an intelligent solution for predicting student performance using supervised machine learning algorithms. This proposed focus on addressing the limitations of existing prediction models and enhancing prediction accuracy. In this work employed three supervised machine learning algorithms: Random Forest, Extra Trees, and K-Nearest Neighbors. The steps of research methodology contained (data collection, preprocessing, feature identification, model construction, and evaluation). This paper utilized a dataset comprising 24,000 training instances and 6,000 testing instances, applying various preprocessing techniques for data optimization. The Extra Trees algorithm achieved the highest accuracy (98.15%), followed by Random Forest (94.03%) and K-Nearest Neighbors (91.65%). All algorithms demonstrated high precision and recall. Notably, K-Nearest Neighbors exhibited exceptional computational efficiency with a training time of 0.00 seconds. This study proposed an efficient model for prediction student performance. The high accuracy and efficiency of the proposed system highlight its potential for application in educational data mining. The findings of this proposed to improving student success rates in educational institutions by enabling timely and appropriate interventions.